2011
DOI: 10.1007/s00417-011-1795-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreous VEGF-A in eyes with massive vitreous hemorrhage

Abstract: Even with a massive VH, diffusible VEGF does not increase significantly in the liquid phase and is principally present in a clot. VH alone should not be an indication for vitrectomy from the point of view of VEGF-related pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although VEGF is abundant in serum, the levels of VEGF in the vitreous fluid did not differ significantly between eyes with massive vitreous hemorrhage without diabetic retinopathy and nondiabetic eyes without vitreous hemorrhage. On the other hand, the concentration of VEGF was significantly higher in eyes with PDR than in nondiabetic eyes with massive vitreous hemorrhage or nondiabetic eyes with no vitreous hemorrhage [33]. Moreover, in a previous study, we reported that brain-derived neurotrophic factor (BDNF) was not detected in vitreous samples from patients with PDR and nondiabetic control patients, whereas BDNF was detected in all serum samples from patients with PDR and nondiabetic controls [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although VEGF is abundant in serum, the levels of VEGF in the vitreous fluid did not differ significantly between eyes with massive vitreous hemorrhage without diabetic retinopathy and nondiabetic eyes without vitreous hemorrhage. On the other hand, the concentration of VEGF was significantly higher in eyes with PDR than in nondiabetic eyes with massive vitreous hemorrhage or nondiabetic eyes with no vitreous hemorrhage [33]. Moreover, in a previous study, we reported that brain-derived neurotrophic factor (BDNF) was not detected in vitreous samples from patients with PDR and nondiabetic control patients, whereas BDNF was detected in all serum samples from patients with PDR and nondiabetic controls [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although VEGF is abundant in serum, the levels of VEGF in the vitreous fluid did not differ significantly between eyes with nondiabetic massive vitreous hemorrhage and nondiabetic eyes without vitreous hemorrhage. On the other hand, the concentration of VEGF was significantly higher in eyes with PDR than in nondiabetic eyes with massive vitreous hemorrhage or nondiabetic eyes with no vitreous hemorrhage [ 38 ]. Furthermore, in a previous study, we reported that brain-derived neurotophic factor (BDNF) was not detected in vitreous samples from patients with PDR and nondiabetic control patients, whereas BDNF was detected in all serum samples from patients with PDR and nondiabetic controls [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the antiangiogenic effectiveness of UPARANT was assessed in sprouting assays including human umbilical vein endothelial cells (HUVECs) and chick embryo chorioallantoic membrane (CAM) in which sprouting was induced by the vitreous fluid collected from patients with proliferative diabetic retinopathy (PDR). This experimental procedure determines the effective-ness of UPARANT in counteracting angiogenic processes elicited by a milieu that contains high levels of proangiogenic agents [26][27][28] and induces retinal endothelial cell proliferation by acting as a human eye-derived proangiogenic factor. [29][30][31][32]…”
mentioning
confidence: 99%